Benthic remineralisation rates in shelf and slope sediments of the northern Benguela upwelling margin. (1st February 2016) - Neumann, Andreas; Lahajnar, Niko; Emeis, Kay-Christian
Abstract: The Benguela Upwelling System off Namibia is a region of intensive plankton production. Remineralisation of this biomass frequently causes the formation of an oxygen minimum zone. A part of the organic matter is further deposited on the broad shelf in form of an extensive mudbelt with high TOC concentrations. During February 2011 we retrieved sediment samples from shelf and slope sediment along the Namibian coast to establish fluxes of nutrients, oxygen, and N2 on the basis of pore water concentrations. In mudbelt sediment, fluxes were estimated as high as 8 mmol  NH 4 + m −2  d −1 and 0.9 mmol PO 4 3 − m −2  d −1, which is probably attributable to the activity of large sulphur bacteria. Especially phosphate is mobilised from sediment overlain by oxygen deficient bottom water when and where bottom water oxygen concentrations fall below 50 µmol l −1 . In comparison to nutrient transport by Southern Atlantic Central Water flowing onto the Namibian shelf, benthic nutrient fluxes of the mudbelt contribute less than 5% to the nutrient budget of the shelf. Highlights: Benthic fluxes of shelf and slope estimated with pore water profiles. Ensemble comprises fluxes of nutrients, oxygen, and N2 . High efflux of ammonium and phosphate from mudbelt sediment. Low oxygen bottom water triggers phosphate pulses.